2022
DOI: 10.31635/ccschem.021.202100885
|View full text |Cite
|
Sign up to set email alerts
|

Design of High-Contrast Mechanochromic Materials Based on Aggregation-Induced Emissive Pyran Derivatives Guided by Polymorph Predictions

Abstract: High contrast mechanochromic materials are prominent candidates for sensor, security and memory applications; however, the development of materials with a large luminescence change (Δλ em >100 nm) under external stimuli is challenging. Considering that polymorphic molecules usually exhibit reversible mechanochromism, polymorph prediction is adopted for the first time to guide the design of high-contrast mechanochromic materials in this study. We designed and synthesized a series of donor-π-acceptor pyran deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As for the fluorescence bands at 527 and 600 nm, they were ascribed to the monomer and p cluster emissions of nano-particles, which would emit red-shifted fluorescence compared to the monomers in dilute solutions. 41,57,58 The fluorescence properties of its single crystals also match this hypothesis. Similar AIE behaviour was found for MBAV-I (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As for the fluorescence bands at 527 and 600 nm, they were ascribed to the monomer and p cluster emissions of nano-particles, which would emit red-shifted fluorescence compared to the monomers in dilute solutions. 41,57,58 The fluorescence properties of its single crystals also match this hypothesis. Similar AIE behaviour was found for MBAV-I (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Recently, we successfully screened out a series of highcontrast mechanochromic molecules by predicting potential polymorphs. 40,41 Due to the fact that sufficient crystal structures have not been obtained to match the predicted ones, the reliability of this strategy needs to be proved. Our previous studies demonstrated that a D-p-A molecule has a higher potential to emit polymorphism-dependent fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current focus is limited to local modification of existing organic fluorophores. 10 The strategy commonly employed for this involves the introduction of long alkyl chains, 11 or different substituents to fluorophores, as well as altering donor-receptor interactions [12][13][14] or substituent positions. Substituents can adapt the response of solid fluorescent molecules to stimuli and influence the fluorescence quantum yield, [15][16][17] whereas introducing long alkyl chains can play an important role in regulating the photoelectric properties of fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A TPE-dioxaborine fluorophore reported by Yang et al with four polymorphs and one amorphous solid state exhibited four emission colors ranging from green to red . Xiao and Yi et al also designed high-contrast MRL materials by polymorph prediction. , …”
Section: Introductionmentioning
confidence: 99%
“…23 Xiao and Yi et al also designed high-contrast MRL materials by polymorph prediction. 24,25 As the most concerned aggregation-induced emission (AIE) group, TPE has always been favored by researchers because of its unique advantages, and many TPE derivatives were found to be polymorphous. The blue fluorescence of TPE could be easily regulated by introducing strong electron-donating and electronaccepting groups.…”
Section: Introductionmentioning
confidence: 99%